Gender and socio-ecological resilience to climate change : a transformative approach in selected post-fast track resettlement farms in Zvimba East District, Mashonaland West Zimbabwe - Thebe, Vusilizwe (University of Pretoria, 2024)
Thesis (PhD (Development Studies))--University of Pretoria, 2023.